Envelhecimento compartilhado: participação de idosas no grupo de convivência da comunidade Nova Pantanal - Graciani, Juliana Santos (2009)
This study is aimed to reflect on the aging process in the elderlies and the importance of participation in the Group of Women Living Project Bus Entertaiment-Bau Encantado, an intervention by the Community Works of PUC / SP Center, built on the assumption that the aging is a process involving the biopsychosocial dimensions. In the globalized society aging can foster exclusion but point also to the possibility of social and community participation as a strategy for coping with inequality. It has been used qualitative methodology and procedures in this research, as the method of participant observation and interviews. The fieldwork has been conducted in the New Community Pantanal, with elderly women participants from the Group of Women Living. The choice of participants has been based upon the time which they have integrated into the group and their self-acceptance of taking part in the Project study. The analysis has been conducted taking into consideration four major categories from the data gathered: personal relationships, family, community and their relationship with the aging process. The discussion of the data collected revealed that the family occupies a central space into their lives where special emphasis is given to the husbands. Domestic violence is also considered as part of reality. Old age appears as a natural stage of human development, mainly associated with diseases and physical disabilities. It s recognize the situation of rights violation and their relationship with the reality of poverty. The participation in the project is valued for promoting personal change in terms of self-confidence, self-esteem, self-recovery and availability of income to support their family. Highlights also the importance of social viewpoint where participation is needed in order to promote the necessary neighborhood changes. The Group of Women Living has been a social space to overcome the fear of learning new skills, the conquest of sociability, the practice of solidarity and the possibility of acquiring a new profession. Therefore, from taking part in the Living Group the elderly establishes new relationship with themselves, with their own aging process, among the group and the community, creating a new role and social function